RESULTS OF QUICK DETECTION OF DIABETES ON ELDERLY AT SOME COMMUNES IN THAI NGUYEN CITY (Vietnam Journal of Community Medicine, 2021)
Objectives: Describe the rate of diabetes by rapid detection on elderly in some communes of ThaiNguyen city.Materials and Methods: A cross-sectional study had been conducted on 520 elderly.Results: The rate of diabetes in the elderly in the 7 studied communes is 23.6%, of which 12.1% isnew discovery through rapid test. The proportion of subjects with pre-diabetes accounts for 19.5%,of which 8.3% are fasting blood glucose disorders and 11.2% are impaired glucose tolerance. Thehighest prevalence of diabetes is found in the age group 60-69 (26.6%); in which, Tich Luong wardhas the highest rate of diabetic subjects (32.8%) and Linh Son commune has the lowest rate ofdiabetic subjects (15.4%). There were 417 subjects (80.19%) that complied with the required fastingtime with the highest blood sugar test result of 16.3 mmol /l, of which 35.5% of subjects who fastedfor 8 hours or more had blood glucose test ≥7 mmol /l. As a result, adding a glucose tolerance testrevealed 13 more subjects (accounting for 11.4%) with diabetes.Conclusion: It is necessary to apply the rapid testing for blood sugar to all at-risk subjects, elderlyin community.
Keywords: Quick detection of diabetes, Elderly, Thai Nguyen City